Re: Placental histological patterns and uterine artery Doppler velocimetry in pregnancies complicated by early or late pre‐eclampsia. R. Orabona, C. M. Donzelli, M. Falchetti, A. Santoro, A. Valcamonico and T. Frusca. Ultrasound Obstet Gynecol 2016; 47: 580–585. (May 2016) - Sebire, N. J.
Abstract : Linked Comment: Ultrasound Obstet Gynecol 2016; 47: 580–585